Development of an Advanced Drug Delivery System for Protein- and Peptide-Based Therapeutics - Lai, Wen Faye; Kee, Phei Er; Ming, Long Chiau; Chew, Yik-Ling; Lee, Siew-Keah; Bostanudin, Mohammad F.; Uddin, A.B.M. Helal; Liew, Kai Bin (Current Pharmaceutical Design, 2025)
Advancements in biotechnology have played a key role in driving the development of protein- and peptide-based therapeutics. Drug delivery systems (DDSs) designed for proteins and peptides are carefully crafted to improve drug stability, enhance bioavailability, and reduce toxic side effects by ensuring precise delivery to targeted areas. However, despite their promising therapeutic potential, protein- and peptide-based drugs face substantial challenges due to their distinct physicochemical properties and biological barriers. Ongoing developments in protein- and peptide-based DDSs present valuable solutions to address these challenges, ultimately improving drug stability, delivery accuracy, and therapeutic efficacy. Researchers are actively working on creating innovative carrier technologies to further enhance the effectiveness and precision of these therapeutics. This review examines the wide-ranging applications of protein- and peptide-based therapeutics, explores advanced drug delivery techniques, and highlights various administration routes aimed at overcoming existing obstacles. In conclusion, this review offers a comprehensive understanding of protein- and peptide-based therapeutics as a viable alternative to conventional drug delivery systems, harnessing the power of cutting-edge biotechnological advancements.
Keywords: enzymes